An overview of traditional Chinese medicine affecting gut microbiota in obesity - Li, Donghui; Tang, Weiwei; Wang, Yanyan; Gao, Qi; Zhang, Hongwei; Zhang, Yu; Wang, Yuliang; Yang, Yongyi; Zhou, Yingming; Zhang, Yike; Li, Haonan; Li, Shuo; et al. (Frontiers in Endocrinology, 2023)
Obesity, a chronic metabolic disease with a complex pathophysiology, is caused by several variables. High-fat diets lead to disruption of the gut microbiota and impaired gut barrier function in obese people. The dysbiosis and its metabolites through the intestinal barrier, leading to an imbalance in energy metabolism and inflammatory response, which eventually contributes to the development of chronic diseases such as diabetes, hypertension, and cardiovascular disease. The current medicines are therapeutic to obesity in short-term, however, they may bring significant physical and emotional problems to patients as major side effects (Krentz et al., 2016; Fan et al., 2021). Therefore, it is urgent to explore new therapeutic methods that have definite efficacy, can be taken for a long time, and have mild adverse effects. Numerous studies have demonstrated that traditional Chinese medicine (TCM) can control the gut microbiota in a multi-targeted and comprehensive manner, thereby restoring flora homeostasis, repairing damaged intestinal mucosal barriers and eventually curbing the development of obesity. The active ingredients and compounds of TCM can restore the normal physiological function of the intestinal mucosal barrier by regulating gut microbiota to regulate energy metabolism, inhibit fat accumulation, affect food appetite, reduce intestinal mucosal inflammatory response, thereby effectively playing a weight loss role and providing new strategies for obesity prevention and treatment. Although there are some studies on the regulation of gut microbiota by TCM to prevent and treat obesity, all of them have the shortcomings of being systematic and comprehensive. Therefore, this work comprehensively describes the molecular mechanism of obesity mediated by gut microbiota based on the research state of obesity, gut microbiota, and TCM. A comprehensive and systematic summary of TCM targeting the regulation of gut microbiota for the treatment of obesity should be conducted in order to provide new strategies and ideas for the treatment of obesity.